2002
DOI: 10.1111/j.1151-2916.2002.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manganese Ion Diffusion on the Microstructural Evolution of Lead Lanthanum Zirconate Titanate Ceramic

Abstract: Microstructural evolution of lead lanthanum zirconate titanate (PLZT) ceramics caused by diffusion of the Mn ion was observed. Specimens with layered structures were fabricated by copressing a PLZT powder (9/65/35) doped with Mn and same PLZT powder without the dopant. When the copressed specimen was sintered at 1200°C in air, the Mn ion diffused out of the doped region. The region originally containing the Mn ions was totally free of pores while all other regions remained porous. The formation of lattice vaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Perez-Delfin et al [7] reported that Mn-acceptor doping in bulk PLZT (9/65/35) resulted in increased coercive field, reduced dielectric permittivity, decreased remanent polarization, and lessened temperature dependence. Choi et al [8] reported improved densification at the boundary of Mn-doped and undoped regions, and suggested that low-level (<2 mol.%) doping can enhance dielectric properties. Our recent study [9] showed that thin insertion layers of ZrO 2 can effectively reduce leakage current density and improve the dielectric performance under a bias field.…”
Section: Introductionmentioning
confidence: 99%
“…Perez-Delfin et al [7] reported that Mn-acceptor doping in bulk PLZT (9/65/35) resulted in increased coercive field, reduced dielectric permittivity, decreased remanent polarization, and lessened temperature dependence. Choi et al [8] reported improved densification at the boundary of Mn-doped and undoped regions, and suggested that low-level (<2 mol.%) doping can enhance dielectric properties. Our recent study [9] showed that thin insertion layers of ZrO 2 can effectively reduce leakage current density and improve the dielectric performance under a bias field.…”
Section: Introductionmentioning
confidence: 99%